Technical economic estimate of the ratio of cooling welding using models vs. MEF - Pinilla, Alexander (2016)
The development of this research paper is focused on a comparison between the results obtained experimentally for the estimation of the rate of cooling water welded geometry T specimens made of structural steel ASTM HR A36 compared to analyzes using computational tools , particularly the software of the finite element modeling (FEM) ANSYS, the experimental test for type K thermocouples which capture the cooling temperature values obtained by the data acquisition cards are used, the analysis model required MEF the development of a more than 850,000 mesh nodes, the results of the comparative product analysis of the cooling rate, showing a difference between methods below 3%, which allows the computer to estimate as a reliable alternative when setting this type of analysis additionally the costs associated with the development of experimental tests vs MEF implementing models for the costs associated with this stage of experimentation are determined, it is established that the rate of recovery, just to test cooling is evaluated 15 months, but the versatility of this computational tool, allows you to explore other uses.